Pengaruh Word of Mouth, Brand Trust, dan Brand Awareness, Terhadap Keputusan Pembelian: Studi Kasus Konsumen Liquid Foom di Kota Surabaya - Irfan Alip Effendi; Lestari Lestari (Economic Reviews Journal, 2026)
This Study aims to examine the influence of Word of Mouth, Brand Trust, and Brand Awarennes on purchasing decisions of liquid FOOM products in Surabaya. The research employed a quantitative approach using a survey method with questionnaires distributed to 100 consumers who had used Liquid FOOM, selected through purposive sampling. The results indicate that recommendations form the surrounding environment, trust in the brand, and brand recognition play an important role in shaping consumer purchasing decisions. The combination of these factors encourages consumers to choose and repurchase Liquid FOOM amid the increasing competition in the vape liquid market